Pemanfaatan Media Sosial Pada Pimpinan Daerah Aisyiyah Lamongan - Darianto Darianto; Arfiana Dewi; Ninin Nike Pebriyati; Yuliana Tri Ratnasari (Pusat Riset dan Inovasi Nasional, 2021)
This article discusses social media content design training organized by the Lamongan Aisyiyah Regional Leadership (PDA), in collaboration with the Ahmad Dahlan Lamongan Institute of Technology and Business. The focus of utilization training is managing Instagram feeds and color choices. Participants, the majority of whom are women aged 30-45 years, act as contributors to the PDA Lamongan Instagram account. Material includes feed management, use of color pallette. The results of this training show an increased understanding of Instagram. The enthusiasm of the participants reflects the success of the training on utilizing PDA Lamongan social media by applying the knowledge gained, opening up the potential for similar activities in the future